Self-supporting integrated electrode material derived from wood charcoal as well as preparation method and application of self-supporting integrated electrode material

By growing the heterostructure of nickel nanoparticles embedded in molybdenum nitride in situ on wood charcoal, the problems of high cost of precious metal-based electrode materials and low catalytic activity of transition metal alloys in the existing electrolytic water hydrogen production technology are solved, and high efficiency and stable electrocatalytic performance and low-cost large-scale production are achieved.

CN119753736AActive Publication Date: 2025-04-04SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411852380.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, precious metal-based electrode materials have high cost, limited reserves and poor stability, and transition metal alloys and their oxides have low catalytic activity, making it difficult to achieve large-scale application.

Method used

The self-supported integrated electrode material derived from charcoal was synthesized by hydrothermal synthesis and high-temperature ammonia mixed gas reduction method. The heterostructure of nickel nanoparticles embedded in molybdenum nitride was grown on charcoal in situ, improving electrocatalytic activity and stability.

Benefits of technology

In the electrolytic water reaction under alkaline conditions, the efficient catalytic performance and structural stability of the electrode material are achieved, which reduces power consumption and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753736A_ABST
    Figure CN119753736A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting integrated electrode material derived from wood charcoal as well as a preparation method and application of the self-supporting integrated electrode material. The preparation method comprises the steps that S1, after lignin is removed from poplar slices, the poplar slices are placed in a protective atmosphere to be carbonized, and three-dimensional porous carbonized wood derived from wood charcoal is obtained; s2, preparing a mixed solution containing a nickel source and a molybdenum source; s3, preparing an electrode material precursor of molybdenum-nickel oxide growing on the wood charcoal by using the three-dimensional porous wood charcoal and the mixed solution; s4, performing high-temperature ammonia gas reduction on the precursor to obtain a wood charcoal derived self-supporting integrated electrode material; the invention also discloses application of the electrode material in water electrolysis hydrogen production. The electrode material is synthesized by adopting a hydrothermal synthesis method and a high-temperature ammonia gas mixed gas reduction method, a heterostructure with nickel nanoparticles embedded into molybdenum nitride nanosheets grows on wood charcoal in situ, and by combining rapid substance transfer of a porous wood charcoal structure, an electronic structure can be adjusted, a water dissociation energy barrier is reduced, and the electrochemical performance of the electrode material is improved. And the composite material has excellent electrocatalytic activity and stability on an electrolytic water reaction under an alkaline condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to a self-supporting integrated electrode material derived from wood charcoal, and a preparation method and application thereof. Background Art

[0002] The large-scale burning of fossil fuels such as coal, oil and natural gas has led to serious environmental pollution, and these resources are limited and difficult to regenerate. Therefore, it has become a top priority to study clean, renewable new energy and energy storage equipment; among them, hydrogen is considered to be one of the most promising energy carriers due to its light weight, high calorific value, pollution-free combustion and sustainable utilization. However, hydrogen energy is not an energy resource that exists in large quantities in nature, but needs to be produced. Among the many methods for producing hydrogen, the electrolysis of water has a simple preparation process, is clean and pollution-free, and has a relatively mature technology. It is one of the well-known and recognized hydrogen production methods.

[0003] Water electrolysis (OWS) is a complex process involving gas-liquid-solid three-phase interface reactions. In order to maximize the utilization of active substances, accelerate gas-liquid transport, and improve electrocatalytic activity and stability, the design and selection of electrode structure and surface properties are crucial. Nowadays, nickel foam and copper foam materials are widely used in three-dimensional porous supports to grow electrode materials in situ, but they are expensive and susceptible to corrosion in complex electrolysis environments.

[0004] OWS involves two half reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). However, the evolution reaction rates of hydrogen and oxygen are slow, which limits the catalytic efficiency. Currently, the power consumption of hydrogen production by water electrolysis is 4.5-5.5 kWh / Nm 3 H2, the main reason is that the energy consumption of the anode oxygen production reaction is high. According to research, using high-efficiency catalytic electrode materials to reduce the reaction activation energy can effectively reduce energy consumption. Therefore, in the electrolysis of water to produce hydrogen, how to improve the activity of electrode catalytic materials, reduce the overpotential of hydrogen evolution reaction, and improve the stability of electrode materials is the key.

[0005] Existing Pt / C electrode materials have excellent hydrogen evolution catalytic performance, and precious metal-based RuO2 and IrO2 electrode materials perform well in oxygen evolution catalysis. However, these precious metal-based electrode materials face the problems of high cost, limited reserves and poor long-term stability, which restrict their large-scale application. In contrast, transition metal alloys and their oxides are attractive as potential alternative materials due to their low cost and abundant reserves. However, the catalytic activity of transition metals and their oxides is still far behind that of precious metals. Therefore, how to achieve controllable design in transition metal alloys and their oxides to improve catalytic activity is an urgent problem to be solved in this field. Summary of the invention

[0006] The present invention aims to provide a self-supporting integrated electrode material derived from wood charcoal, and a preparation method and application thereof. The self-supporting integrated electrode material derived from wood charcoal is synthesized by a hydrothermal synthesis method and a high-temperature ammonia mixed gas reduction method, and a heterogeneous structure of nickel nanoparticles embedded in molybdenum nitride is in situ grown on wood charcoal, which exhibits excellent electrocatalytic activity and stability in water electrolysis reaction under alkaline conditions to solve the above-mentioned problems.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a self-supporting integrated electrode material derived from wood charcoal comprises the following steps:

[0009] S1. Slice the poplar wood along its vertical growth direction, perform delignification treatment, and then carbonize it in a protective atmosphere to obtain a three-dimensional porous wood charcoal derived from wood charcoal;

[0010] S2, firstly disperse the nickel source and the molybdenum source in the solvent respectively, stir to make them fully dissolved; then mix the two to obtain a mixed solution;

[0011] S3, transferring the three-dimensional porous wood charcoal obtained in step S1 and the mixed solution obtained in step S2 to a high-pressure reactor for reaction, cooling to room temperature after the reaction is completed, washing with deionized water, and drying with forced air to obtain an electrode material precursor in which molybdenum-nickel oxide grows on wood charcoal;

[0012] S4. Placing the electrode material precursor obtained in step S3 in a tube furnace and reducing it at high temperature in a mixed atmosphere containing ammonia, thereby obtaining the desired self-supporting integrated electrode material derived from wood charcoal.

[0013] Furthermore, in S1, the length*width*height of the poplar wood slice is 2-6 cm×1-3 cm×0.1-0.3 cm, preferably 4 cm×2 cm×0.1 cm; the solution for removing lignin is a high-temperature sodium hypochlorite aqueous solution, the temperature is 80-120° C., and the concentration of sodium hypochlorite is 0.1-0.5 mol / L; the protective atmosphere is one of Ar2 or N2, the flow rate of the protective atmosphere is 30-120 mL / min, the carbonization temperature is 300-1000° C., the heating rate is 1-20° C. / min, and the carbonization time is 1-15 h.

[0014] Further, in S2, the nickel source is one of sulfate, oxalate, nitrate, halide, acetate, acetylacetonate soluble salt; the molybdenum source is molybdate; the solvent is one of analytical grade ethanol, ethanolamine, diethanolamine, triethanolamine, N,N-dimethylformamide, ethylenediamine alkaline soluble solvent and aqueous solution diluted with deionized water. The concentration of the nickel source in the solvent is: 0.01mol / L to 0.05mol / L; the concentration of the molybdenum source in the solvent is: 0.01mol / L to 0.15mol / L.

[0015] Furthermore, in S2, the molar ratio of the added nickel source to the molybdenum source is 1:0.1-3.

[0016] Furthermore, in S3, the reaction temperature in the high-pressure reactor is 120 to 200°C, and the reaction time is 1 to 36 hours.

[0017] Further, in S4, the reaction temperature in the tube furnace is 200-700° C., the reaction time is 0.5-5 h, and the mixed gas containing ammonia and nitrogen or ammonia and argon has a flow rate of 30-120 mL / min.

[0018] The self-supporting integrated electrode material derived from wood charcoal prepared by the above-mentioned preparation method of the self-supporting integrated electrode material derived from wood charcoal has a heterogeneous structure in which nanoparticles are embedded in nanosheet layers, a three-dimensional hierarchical porous structure, low-curvature microchannels, adjustable hydrophilicity / hydrophobicity and good mechanical properties, good conductivity and high specific surface area.

[0019] The application of the self-supporting integrated electrode material derived from wood charcoal prepared by the method for preparing the self-supporting integrated electrode material derived from wood charcoal in hydrogen production by electrolysis of water.

[0020] The beneficial effects of the technical solution are:

[0021] 1. The present invention adopts a hydrothermal synthesis method and a high-temperature ammonia mixed gas reduction method to synthesize a self-supporting integrated electrode material derived from wood charcoal. The three-dimensional porous wood charcoal derived from the wood charcoal has good conductivity and high specific surface area, and can provide more reaction active sites and electron transmission channels; molybdenum nickel oxide grows on the electrode material precursor of the wood charcoal, which can increase the energy storage capacity and electrochemical activity of the electrode material; the electrode material has good structural stability and mechanical strength, and can effectively resist volume expansion and structural damage; and the preparation method is simple and easy, low in cost, and suitable for large-scale production.

[0022] 2. The self-supporting integrated electrode material derived from wood charcoal prepared by the present invention is synthesized by changing the ratio of transition metal nickel / molybdenum raw materials and the reduction temperature of the mixed gas to synthesize a heterogeneous structure electrocatalyst with a special embedding method. Combined with the rapid material transport of the porous wood charcoal structure, the obtained catalyst has a high specific surface area and high intrinsic electrochemical activity, which is beneficial to the contact between the catalyst and the water molecules in the electrolyte and promotes the electrolysis reaction of water molecules.

[0023] 3. The self-supporting integrated electrode material derived from wood charcoal prepared by the present invention is used as an electrode material for electrolytic hydrogen production. Since the electrode material has a heterogeneous structure in which nanoparticles are embedded in nanosheet layers, the activity of active sites can be improved while exposing more active sites, thereby improving the electrocatalytic activity. At the same time, its morphology can be optimized by controlling the concentration of reactants, the temperature of the high-temperature reduction reaction of the mixed gas, and the reaction time, with good repeatability. The obtained catalyst has a high specific surface area and high intrinsic electrochemical activity, which is beneficial for the catalyst to contact with water molecules in the electrolyte and promote the electrolysis reaction of water molecules.

[0024] 4. The self-supporting integrated electrode material derived from wood charcoal prepared by the present invention constructs an efficient gas-liquid-solid three-phase reaction interface for water electrolysis due to its three-dimensional hierarchical porous structure, low-curvature microchannels, adjustable hydrophilicity / hydrophobicity and good mechanical properties. In addition, the use of wood charcoal as a substrate is conducive to further reducing large-scale production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Flow chart for preparing wood charcoal derived self-supporting integrated electrode materials for the present invention.

[0026] Figure 2 1 is the XRD diagram of DWC in Example 1 and Ni / MoN@DWC in Example 2 of the present invention.

[0027] Figure 3 This is the SEM image of DWC in Example 1 of the present invention.

[0028] Figure 4 The SEM / TEM image and selected electron diffraction image of the electrode material prepared in Example 2 of the present invention.

[0029] Figure 5 This is the EDS image of Ni / MoN@DWC in Example 2 of the present invention.

[0030] Figure 6 HER performance diagram and HER overpotential diagram of the electrode materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention and the commercial Pt / C catalyst.

[0031] Figure 7The OER performance diagram and OER overpotential diagram of Ni / MoN@DWC and commercial RuO2 catalyst in Example 2 of the present invention.

[0032] Figure 8 This is the water electrolysis performance diagram of Ni / MoN@DWC / / Ni / MoN@DWC water electrolysis hydrogen production and commercial Pt / C / / RuO2 in Example 2 of the present invention, and the water electrolysis stability diagram of Ni / MoN@DWC / / Ni / MoN@DWC.

[0033] Fig. 9 The Ni / MoN@DWC / / Ni / MoN@DWC in Example 2 of the present invention is actually assembled into a water electrolysis device.

[0034] Fig.10 This is a graph showing the test results of the long-term hydrogen evolution stability of the Ni / MoN@DWC assembled water electrolysis hydrogen production device at different current densities in Example 2 of the present invention and an actual schematic diagram. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:

[0036] Example 1

[0037] The three-dimensional porous wood charcoal was prepared as follows:

[0038] Pretreatment of natural wood: first slice the natural poplar wood perpendicular to its growth direction, the length * width * height of the slice is 4cm×2cm×0.1cm; then clean the slices, soak them in 0.2mol / L sodium hypochlorite solution for 2 hours, and then dry them in a forced air drying oven at 80℃ overnight; preparation of three-dimensional porous conductive wood charcoal: place the dried slices in a quartz tube furnace, pass nitrogen, and heat to 500℃ at a rate of 5℃ / min for carbonization for 1.5h, then heat to 900℃ and carbonize for another 1h to obtain three-dimensional porous conductive wood charcoal derived from wood charcoal, recorded as DWC.

[0039] Example 2

[0040] The three-dimensional porous wood charcoal was prepared as follows:

[0041] Pretreatment of natural wood: first slice the natural poplar wood perpendicular to its growth direction, the length * width * height of the slice is 4cm×2cm×0.1cm; then clean the slices, soak them in 0.2mol / L sodium hypochlorite solution at 110℃ for 1 hour, and then dry them in a forced air drying oven at 80℃ overnight; Preparation of three-dimensional porous conductive wood charcoal: place the dried slices in a quartz tube furnace, pass nitrogen, heat to 500℃ at a rate of 5℃ / min, carbonize for 1.5h, then heat to 900℃ and carbonize for another 1h to obtain three-dimensional porous conductive wood charcoal derived from wood charcoal;

[0042] Preparation of a mixed solution containing a nickel source and a molybdenum source: 1 mmol NiCl2·6H2O and 2 mmol Na2MoO4·2H2O were added into 15 mL of deionized water respectively, stirred to dissolve, and then the two were mixed into a homogeneous mixed solution;

[0043] Growth of bimetallic oxides on three-dimensional porous wood charcoal: The homogeneous mixed solution and conductive wood charcoal were transferred to a stainless steel autoclave containing 50 mL of polytetrafluoroethylene lining, which was then sealed and heated at 150°C for 12 h; after cooling to room temperature, the sample was taken out, washed several times with deionized water, and then dried at 60°C for 12 h to obtain an electrode material precursor of molybdenum nickel oxide grown on wood charcoal;

[0044] Preparation of self-supporting integrated electrode materials derived from wood charcoal: The electrode material precursor in which molybdenum nickel oxide is grown on wood charcoal is placed in a tubular furnace, and an ammonia / argon mixed gas is introduced. The temperature is raised to 500°C at a heating rate of 3°C / min, and then kept warm for 2 hours. The temperature is cooled to room temperature to obtain the desired self-supporting integrated electrode material derived from wood charcoal, which is recorded as Ni / MoN@DWC.

[0045] Comparative Example 1

[0046] A method for preparing a self-supporting integrated electrode material derived from wood charcoal comprises the following steps:

[0047] Preparation of three-dimensional porous wood charcoal: first, slice natural poplar wood perpendicular to its growth direction, the length * width * height of the slice is 4cm × 2cm × 0.1cm, and soak it in 0.2mol / L sodium hypochlorite solution at 110℃ for 1 hour; then clean the slices and dry them in a forced air drying oven at 80℃ overnight; finally, place the dried slices in a quartz tube furnace, pass nitrogen, heat to 500℃ at a rate of 5℃ / min, carbonize for 1.5h, and then heat to 900℃ and carbonize for another 1h to obtain three-dimensional porous conductive wood charcoal derived from wood charcoal;

[0048] Preparation of a mixed solution containing a nickel source and a molybdenum source: 1 mmol NiCl2·6H2O and 2 mmol Na2MoO4·2H2O were added into 15 mL of deionized water respectively, stirred to dissolve, and then the two were mixed into a homogeneous mixed solution;

[0049] Growth of bimetallic oxides on three-dimensional porous wood charcoal: The homogeneous mixed solution and conductive wood charcoal were transferred to a stainless steel autoclave containing 50 mL of polytetrafluoroethylene lining, which was then sealed and heated at 150°C for 12 h; after cooling to room temperature, the sample was taken out, washed several times with deionized water, and then dried at 60°C for 12 h to obtain an electrode material precursor of molybdenum nickel oxide grown on wood charcoal;

[0050] Preparation of self-supporting integrated electrode materials derived from wood charcoal: Place the electrode material precursor in which molybdenum nickel oxide is grown on wood charcoal in a tubular furnace, introduce an ammonia / argon mixture, heat the temperature to 500°C at a heating rate of 3°C / min, keep the temperature for 2 hours, and cool to room temperature to obtain the desired self-supporting integrated electrode material derived from wood charcoal. Soak the material in 0.5 M sulfuric acid for 1 hour, wash with pure water until neutral, and then dry to obtain a sample, which is recorded as MoN@DWC.

[0051] Comparative Example 2

[0052] A method for preparing a self-supporting integrated electrode material derived from wood charcoal comprises the following steps:

[0053] Preparation of three-dimensional porous wood charcoal: first, slice natural poplar wood perpendicular to its growth direction, the length * width * height of the slice is 4cm × 2cm × 0.1cm, and soak it in 0.2mol / L sodium hypochlorite solution at 110℃ for 1 hour; then clean the slices and dry them in a forced air drying oven at 80℃ overnight; finally, place the dried slices in a quartz tube furnace, pass nitrogen, heat to 500℃ at a rate of 5℃ / min, carbonize for 1.5h, and then heat to 900℃ and carbonize for another 1h to obtain three-dimensional porous conductive wood charcoal derived from wood charcoal;

[0054] Preparation of a mixed solution containing a nickel source and a molybdenum source: Add 3 mmol NiCl2·6H2O into 30 mL deionized water and stir evenly.

[0055] Growth of bimetallic oxides on three-dimensional porous wood charcoal: The homogeneous mixed solution and conductive wood charcoal were transferred to a stainless steel autoclave containing 50 mL of polytetrafluoroethylene lining, which was then sealed and heated at 150°C for 12 h; after cooling to room temperature, the sample was taken out, washed several times with deionized water, and then dried at 60°C for 12 h to obtain an electrode material precursor of molybdenum nickel oxide grown on wood charcoal;

[0056] Preparation of self-supporting integrated electrode materials derived from wood charcoal: The electrode material precursor in which molybdenum nickel oxide is grown on wood charcoal is placed in a tubular furnace, and an ammonia / argon mixed gas is introduced. The temperature is raised to 500°C at a heating rate of 3°C / min, and then kept warm for 2 hours. The temperature is cooled to room temperature to obtain the desired self-supporting integrated electrode material derived from wood charcoal, which is recorded as Ni@DWC.

[0057] Performance Test:

[0058] The electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention were characterized: X-ray diffraction (XRD) was used to analyze the crystal structure and possible phase composition of the synthesized various catalyst samples, a field emission scanning electron microscope (SEM) was used to observe the microstructure and morphology of the electrode materials, a high-resolution transmission electron microscope (TEM) was used to characterize the internal structure of the electrode materials, and energy dispersive X-ray spectroscopy (EDS) was used to study the elemental composition of the electrode materials.

[0059] Depend on Figure 2 It can be seen that the broader XRD diffraction peaks at 22° and 44° are attributed to the porous wood charcoal (DWC) framework with low curvature; the XRD diffraction peaks at 32.4°, 36.6°, 49.6° and 41.7°, 45.0° are attributed to the (002), (200), (202) crystal planes of MoN and the (002), (101) crystal planes of Ni, respectively.

[0060] Figure 3 In the figure, a, b, and c are SEM images along the pore growth direction; d, e, and f are SEM images perpendicular to the pore growth direction; Figure 3 As can be seen from a, b, c, d, e and f, the porous and low-curvature radial channel microstructure of the DWC framework generated by the high-temperature carbonization process after delignification of wood is retained.

[0061] Figure 4 In the figure, a, b, c, d, e, and f are SEM images of Ni / MoN@DWC in Example 2; h and i are TEM images of Ni / MoN@DWC in Example 2; and j is a selected electron diffraction image of Ni / MoN@DWC in Example 2;

[0062] Depend on Figure 4 From a, b, and c, it can be seen that Ni / MoN@DWC grows uniformly on the vertical pipe surface of DWC;

[0063] Depend on Figure 4 As shown in d, e, and f, the Ni nanoparticles are embedded in the MoN sheets and are evenly and densely distributed inside the DWC pipe;

[0064] Depend on Figure 4From h and i, we can see that the Ni nanoparticles are embedded in the MoN sheets and are evenly and densely distributed on the DWC porous framework;

[0065] Depend on Figure 4 It can be seen from Figure j that Ni nanoparticles are wrapped by highly defective MoN to form a heterostructure in which Ni is embedded in MoN;

[0066] Depend on Figure 4 It can be seen from Fig. 1 that the lattice spacings of 0.271, 0.239, and 0.199 nm in Ni / MoN@DWC belong to the (002), (121) and (101) crystal planes of MoN, respectively;

[0067] Depend on Figure 5 It can be seen that C, N, Ni and Mo are uniformly distributed in Ni / MoN@DWC, which proves the successful introduction and uniform distribution of Ni / MoN.

[0068] Figure 6 In the figure, a is the HER performance diagram, and b is the HER overpotential diagram.

[0069] Depend on Figure 6 As can be seen from Figure a, Ni / MoN@DWC has the best HER activity.

[0070] Depend on Figure 6 As shown in Figure 2, Ni / MoN@DWC only needs an ultra-low overpotential of 36 mV and 149 mV to obtain 10 mA cm -2 and 100mA·cm -2 This performance is much better than Ni@DWC (η 10 =154mV,η 100 =404mV), MoN@DWC(η 10 =221mV,η 100 =395mV), commercial Pt / C (η 10 =56mV,η 100 =253mV).

[0071] Depend on Figure 7 From a (OER performance diagram), we can see that Ni / MoN@DWC has the best OER activity;

[0072] Depend on Figure 7 As shown in Figure b (OER overpotential diagram), Ni / MoN@DWC only needs low overpotentials of 304 mV and 385 mV to obtain 10 mA cm -2 and 100mA·cm -2 The current density is better than that of commercial RuO2 (η 10 =318mV,η 100 =32mV).

[0073] like Figure 8 and Fig. 9 ( Fig. 9 As shown in (a) for the anode and (b) for the cathode, the Ni / MoN@DWC two-electrode system consists of two identical Ni / MoN@DW electrodes as the anode and cathode, respectively, to form a Ni / MoN@DWC / / Ni / MoN@DWC water electrolysis hydrogen production device, where the cathode produces hydrogen and the anode produces oxygen. For comparison, commercial Pt / C and commercial RuO2 form a Pt / C / / RuO2 water electrolysis hydrogen production device. The Ni / MoN@DWC / / Ni / MoN@DWC water electrolysis hydrogen production device only requires 1.56 and 1.70 V to obtain 10 and 50 mA cm -2 The electrolysis current density of water is 10 mA cm, while the Pt / C / / RuO2 electrolysis water hydrogen production device requires 1.59 and 1.79 V to obtain the same current density; b is the comparison of the electrolysis stability of water. The Ni / MoN@DWC / / Ni / MoN@DWC electrolysis water hydrogen production device has a current density of 10 mA cm -2 After running stably for 35 hours at a current density of and, it can still maintain 94% of the current density.

[0074] Depend on Fig.10 It can be seen that at 10 mA cm -2 Continuous operation for 100 h at a current density of 100 mA cm -2 After continuous operation for 40 h at a current density of , Ni / MoN@DWC electrolyzed water to produce hydrogen without obvious current density decay, showing excellent stability;.

[0075] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a self-supporting integrated electrode material derived from wood charcoal, characterized in that: The following steps are involved: S1, slicing poplar wood along its vertical growth direction, performing delignification treatment, and then carbonizing it in a protective atmosphere to obtain a three-dimensional porous wood charcoal derived from wood charcoal; S2, dispersing the nickel source and the molybdenum source in a solvent respectively, stirring to fully dissolve them; and then mixing the two to obtain a mixed solution; S3, transferring the three-dimensional porous wood charcoal obtained in step S1 and the mixed solution obtained in step S2 to a high-pressure reactor for reaction, cooling to room temperature after the reaction is completed, washing with deionized water, and drying with forced air to obtain an electrode material precursor in which molybdenum-nickel oxide grows on wood charcoal; S4. Placing the electrode material precursor obtained in step S3 in a tube furnace and reducing it at high temperature in a mixed atmosphere containing ammonia, thereby obtaining a self-supporting integrated electrode material derived from wood charcoal.

2. The method for preparing the self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S1, the length*width*height of the poplar wood slice is 2~6cm×1~3cm×0.1~0.3cm.

3. The method for preparing the self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S1, the solution used in the delignification treatment is a high-temperature sodium hypochlorite aqueous solution with a temperature of 80-120° C. and a sodium hypochlorite concentration of 0.1-0.5 mol / L; the protective atmosphere is one of Ar2 or N2; and the flow rate of the protective atmosphere is 30-120 mL / min.

4. The method for preparing the self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S1, the carbonization temperature is 300-1000°C, the heating rate is 1-20°C / min, and the carbonization time is 1-15h.

5. The method for preparing a self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S2, the nickel source is one of sulfate, oxalate, nitrate, halide, acetate, and acetylacetonate soluble salts; the molybdenum source is molybdate; the solvent is one of ethanol, ethanolamine, diethanolamine, triethanolamine, N,N-dimethylformamide, ethylenediamine alkaline soluble solvents and aqueous solutions; the concentration of the nickel source in the solvent is: 0.01mol / L~0.05mol / L; The concentration of the molybdenum source in the solvent is: 0.01mol / L~0.15mol / L.

6. The method for preparing a self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S2, the molar ratio of the added nickel source and molybdenum source is 1:0.1-3.

7. The method for preparing a self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S3, the reaction temperature in the high-pressure reactor is 120 to 200°C, and the reaction time is 1 to 36 hours.

8. The method for preparing a self-supporting integrated electrode material derived from wood charcoal according to claim 1, characterized in that: In S4, the reaction temperature in the tubular furnace is 200-700° C., the reaction time is 0.5-5 h, and the mixed gas containing ammonia and nitrogen or ammonia and argon has a flow rate of 30-120 mL / min.

9. The method according to any one of claims 1 to 8 is used to prepare a self-supporting integrated electrode material derived from wood charcoal, characterized in that: The electrode material has a heterogeneous structure in which nanoparticles are embedded in nanosheet layers, a three-dimensional hierarchical porous structure, low-curvature microchannels, adjustable hydrophilicity / hydrophobicity, and good mechanical properties, and has good conductivity and a high specific surface area.

10. Use of the self-supporting integrated electrode material derived from wood charcoal as claimed in claim 9 in producing hydrogen by electrolysis of water.

Citation Information

Patent Citations

  • Nickel-nickel molybdenum nitride composite catalyst and preparation method and application thereof

    CN114182287A

  • Self-supporting integrated electrode material derived from wood charcoal as well as preparation method and application of self-supporting integrated electrode material

    CN117328084A